The National Galleries of Scotland : Seventieth Report of the Board of Trustees 1976. - The National Gallery of Scotland, Edinburgh (Edinburgh : Trustees of the National Galleries of Scotland, 1977)
Caulfield, Patrick ; Hockney, David ; Jones, David ; Hodler, Ferdinand ; Calder, Alexander ; etc.
Engels
boek